Applications. Communication : for personal and professional contexts - Payne, James, 1950-; Carlin, Diana (Topeka : Clark, 2001)
Communication process; Interpersonal communication; Group communication; Public communication.
Keywords: Applications; Communication -- Study and teaching; Public speaking